2017
DOI: 10.1111/aogs.13122
|View full text |Cite
|
Sign up to set email alerts
|

Term twin birth – impact of mode of delivery on outcome

Abstract: TOL is a good option for women with twin pregnancy at term, regardless of chorionicity. Active management of labor for the second twin is important, also in DC births. Maternal outcomes were more favorable with TOL and although low Apgar scores and low umbilical blood pH may be more frequent after TOL - especially with the second twin - serious neonatal morbidity is rare and does not differ from that after planned CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
3
22
5
Order By: Relevance
“…Our nding of fewer maternal adverse outcomes with CS is in contrast to studies performed by Drassinower et al 18 and Ylilehto et al 19 . Drassinower's study of 1009 twin pregnancies found no signi cant difference in maternal hemorrhage or need for blood transfusion between cases of trial of labor or CS 18 .…”
Section: Discussioncontrasting
confidence: 98%
“…Our nding of fewer maternal adverse outcomes with CS is in contrast to studies performed by Drassinower et al 18 and Ylilehto et al 19 . Drassinower's study of 1009 twin pregnancies found no signi cant difference in maternal hemorrhage or need for blood transfusion between cases of trial of labor or CS 18 .…”
Section: Discussioncontrasting
confidence: 98%
“…Our data showed that CS was significantly associated with postpartum haemorrhage. There were studies supporting our finding that mothers in the CS group were significantly more likely to have hemorrhage and surgical complications 23,29 , whereas other studies showed that mothers were more likely to suffer from haemorrhage with VD 30 . There were also studies with neutral findings showing no significant differences in postpartum haemorrhage rates between CS and VD 31,32 .…”
Section: Maternal Outcomes and Mode Of Deliverysupporting
confidence: 79%
“…However, a recent study found no effect of chorionicity and twin-to-twin DTI on the short-term outcome of second twin after 36 weeks of gestation (Hjortø et al 2014). But there is a risk for substantial bias, as a higher incidence of complications during pregnancy are probably to be found in MC twins and the problematic ones are possibly selected for caesarean section (Ylilehto et al 2017). A higher prevalence of preterm delivery, severe birthweight discordance (>20%), twin-to-twin transfusion syndrome and stillbirths has been found in MC twins (Hoffman et al 2012).…”
Section: Introductionmentioning
confidence: 99%